Kajian Potensi Agroindustri Kelapa di Kabupaten Kolaka Timur – Sulawesi Tenggara - Dhian Herdhiansyah; La Ode Alwi; Asriani (Universitas Djuanda, 2022)
The objectives of this study are to (a) learn about the distribution of coconut agro-industry in East Kolaka Regency, Southeast Sulawesi Province, and (b) find possible raw materials for coconut commodities. This study on the potential of the coconut company used field research (field research), and the research method was quantitative analysis. The possible distribution region for coconut has an average land area of 0.5-1.5 hectares. Coconut is harvested four times each year, with an average yield of 450–1600 pieces. The average coconut output and harvest per tree remains within the normal product range of 25-30 fruit per tree. The potential and distribution of the coconut agro-industry in East Kolaka Regency is established in 5 sub-districts, namely Aere, Ladongi, Lambandia, Loea, and Poli-Polia Districts. The types of products produced are generally copra products with an average income of IDR 2,000,000-IDR 50,000, and the production costs used are IDR 1,000,000-IDR 39,250,000, so that an average of IDR 1,000,000- IDR 17,200,000.